2016
DOI: 10.7903/ijcse.1433
|View full text |Cite
|
Sign up to set email alerts
|

Applying PBL and Zuvio to Enhance English Learning Motivation

Abstract: To inspire college students' English learning motivation, this study proposed to combine Project-Based Learning (PBL) with ZUVIO online teaching platform. The traditional teaching methods focus on teachers' direct instruction in class, which mean that students only receive knowledge from teachers instead of formulating the answers on their own. This also decreases interaction in the classroom and prevents students from collaborating with other peers. However, implementing PBL and ZUVIO would allow students to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…the current research results reveal that the Arab World English Journal www.awej.org ISSN: 2229-9327 15 students felt positive and joyful with the use of Zuvio IRS in class, but it was noticed that the students reported that they are less willing to watch grammar videos after class. This result is consistent with other IRS research findings (Chen, 2014;Khalil & Fahim,2016;Wang, 2016) which reported the IRS' positive effects of formative assessment. The IRS made it possible to assess the degree of students' understanding instantly and assist the teacher to decide how much to explain in detail or proceed to the next part of the lesson.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…the current research results reveal that the Arab World English Journal www.awej.org ISSN: 2229-9327 15 students felt positive and joyful with the use of Zuvio IRS in class, but it was noticed that the students reported that they are less willing to watch grammar videos after class. This result is consistent with other IRS research findings (Chen, 2014;Khalil & Fahim,2016;Wang, 2016) which reported the IRS' positive effects of formative assessment. The IRS made it possible to assess the degree of students' understanding instantly and assist the teacher to decide how much to explain in detail or proceed to the next part of the lesson.…”
Section: Discussionsupporting
confidence: 93%
“…As Chu & Yang (2017) describe, Zuvio is "an online teaching and learning platform which provides a variety of assessment types, including the functions of an instant-response system (IRS)" (p.620). Because students can work in groups and solve problems together with its IRS functions, the Zuvio IRS can increase students' learning motivation by using its online peer assessment system (Wang 2016, Chu & Yang 2017.…”
Section: Application Of Zuvio In L2 Learningmentioning
confidence: 99%
“…The students were more motivated and interested in learning, as similarly found by Chu et al (2017). Meanwhile, Wang (2016) applied PBL to enhance students' motivation using a survey and found that the students were more motivated in learning using PBL as a teaching method. Furthermore, Greenier & Greenier (2018) conducted a study on implementing the 10Cs of the PBL TESOL curriculum and found that both the students and teachers have complementary views on this new curriculum since it is more exciting and engaging than the teacher-centered approach.…”
Section: Introductionsupporting
confidence: 55%
“…According to Leong (2009), PjBL can be utilized to teach Business English in a method that promotes collaborative decision-making and team-building abilities. Wang (2016) discovered that using PjBL in conjunction with an online education platform boosted students' enthusiasm to learn English. (Huang & Wang, 2012) discovered that PjBL was practicable and effective for teaching English interpretation abilities, and that students had favorable attitudes toward PjBL and were eager to learn.…”
Section: Project-based Learning For Grammar Masterymentioning
confidence: 99%